Yin-Chen-Hao Tang Attenuates Severe Acute Pancreatitis in Rat: An Experimental Verification of In silico Network Target Prediction - Xiang, Hong; Wang, Guijun; Qu, Jialin; Xia, Shilin; Tao, Xufeng; Qi, Bing; Zhang, Qingkai; Shang, Dong (Frontiers in Pharmacology, 2016)
Abstract Yin-Chen-Hao Tang (YCHT) is a classical Chinese medicine compound that has a long history of clinical use in China for the treatment of inflammatory diseases. However, the efficacy and mechanisms of YCHT for the treatment of severe acute pancreatitis (SAP) are not known. The current study investigated the pharmacological properties of YCHT against SAP and its underlying mechanisms. A computational prediction of potential targets of YCHT was initially established based on a network pharmacology simulation. The model suggested that YCHT attenuated SAP progress by apoptosis inducement, anti-inflammation, anti-oxidation and blood lipid regulation. These effects were validated in SAP rats. YCHT administration produced the following results: (1) significantly inhibited the secretion of pancreatic enzymes and protected pancreatic tissue; (2) obviously increased the number of in situ terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL)-positive cells and induced apoptosis; (3) markedly inhibited neutrophil infiltration to the impaired pancreas and reduced the inflammatory reaction; (4) notably enhanced the activities of antioxidant enzymes and decreased the nitric oxide synthase (NOS) levels; (5) significantly reduced the levels of triglycerides (TG), total cholesterol (TC) and low-density lipoprotein (LDL) and increased high-density lipoprotein (HDL); and (6) significantly up-regulated peroxisome proliferator-activated receptor-γ (PPARγ) and down-regulated nuclear factor-kappa B (NF-κB). In summary, these results demonstrated that YCHT attenuated SAP progress by inducing apoptosis, repressing inflammation, alleviating oxidative stress and regulating lipid metabolism partially via regulation of the NF-κB/PPARγ signal pathway. Keywords: Yin-Chen-Hao Tang, severe acute pancreatitis, inflammation, apoptosis, network target prediction, PPARγ, NF-κB